Increased Neutrophil-Lymphocyte Ratio and Platelet-Lymphocyte Ratio in Chronic and Severe Urticaria - Sarah Weissmann; Nitzan Burrack; Inbal Golan-Tripto; Amir Horev (Medical Journals Sweden, 2024)
Chronic spontaneous urticaria (CSU) is a disturbing skin condition often severely detrimental to quality of life. Haematological markers of inflammation such as neutrophil-to-lymphocyte and platelet-to-lymphocyte may be used in the assessment of inflammatory skin diseases. Their usefulness in urticaria is unknown. Neutrophil- to-lymphocyte, platelet-to-lymphocyte, and total serum IgE were investigated in urticaria patients: acute spontaneous urticaria (ASU) versus CSU, children versus adults with CSU, and patients with mild-to-moderate versus severe CSU. This retrospective cohort study included patients of all ages diagnosed with urticaria between 2005 and 2020 and blood counts within 30 days of diagnosis. Patients with comorbidities influencing blood cells (infection, surgery, malignancy) were excluded. Neutrophil-to-lymphocyte and platelet-to-lymphocyte were evaluated in patients with ASU vs CSU and mild-to-moderate CSU vs severe CSU (defined by the use of systemic medications or hospitalizations). A total of 13,541 urticaria patients were included in the study. CSU patients (n = 5,021) had higher neutrophil-to-lymphocyte and platelet-to-lymphocyte, as well as serum IgE levels compared with ASU patients (n = 8,520). Adults had higher neutrophil-to-lymphocyte and platelet-to-lymphocyte than children. Severely affected patients (n = 53) had higher neutrophil-to-lymphocyte and platelet-to-lymphocyte compared with mild-to-moderately affected patients (n = 4,968). Patients with higher neutrophil-to-lymphocyte and platelet-to-lymphocyte had higher odds of having CSU rather than ASU and severe urticaria rather mild-to-moderate. In conclusion, neutrophil-to-lymphocyte and platelet-to-lymphocyte are simple and available markers that can be used to predict and assess severe and chronic urticaria.